2009
DOI: 10.1213/ane.0b013e31818c9452
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of a Modified Intertendinous and Classic Posterior Approach to Popliteal Sciatic Nerve Block

Abstract: Potential advantages of the modified intertendinous approach include more rapid onset of anesthesia with an evoked motor response of inversion compared to a classic posterior popliteal sciatic nerve block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Nader et al compared nerve stimulator-guided popliteal sciatic nerve block with a classic approach performed 7 -8 cm to a modified intertendinous approach performed 12 -14 cm above the popliteal crease. They found complete block achieved in 39 of 54 (79.9%) patients in the classic posterior group compared to 44 of 55 (81.5%) patients in the modified intertendinous group [3].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nader et al compared nerve stimulator-guided popliteal sciatic nerve block with a classic approach performed 7 -8 cm to a modified intertendinous approach performed 12 -14 cm above the popliteal crease. They found complete block achieved in 39 of 54 (79.9%) patients in the classic posterior group compared to 44 of 55 (81.5%) patients in the modified intertendinous group [3].…”
Section: Discussionmentioning
confidence: 96%
“…The textbook posterior approach to the distal sciatic nerve is performed approximately inserting a needle 7 -8 cm proximal to the crease formed in the popliteal fossa when the knee is flexed 90 degrees. The technique does not factor in patient characteristics and anatomical variations of the nerve [3]. An anatomical variation in the division of the sciatic nerve is seen as a possible cause for incomplete blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Such injection does not take anatomical variations of the sciatic nerve (SN) into account. Therefore, incomplete block of the sciatic nerve in the popliteal fossa cannot be disregarded (Saleh et al;Nader et al, 2009;Vloka et al, 2001). Accordingly, an anatomical study of the location of the SN in the popliteal fossa is required.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the intertendinous approach involves injection at the midpoint between the tendons of the biceps femoris and the semitendinosus. Some studies have concluded that the intertendinous approach is the more useful of the two Nader et al, 2009). These two approaches to injections at the sciatic nerve are referred to collectively as prebifurcation blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, incomplete block of the sciatic nerve in the popliteal fossa cannot be disregarded (Saleh et al;Nader et al;Vloka et al, 2001). Accordingly, an anatomical study is required on the location of the SN in the popliteal fossa and popliteal crease.…”
Section: Introductionmentioning
confidence: 99%